Vitaminas como redutoras da injúria de herbicidas pós-emergentes na cultura da soja - Vitória Carolina Dantas Alves (2024)
The expansion of soybean cultivation aims to search for alternative management and generates the need to mitigate the phytotoxic effects of the use of herbicides for weed control. Thus, the objective of the study was to evaluate the effects of the exogenous application of thiamine and nicotinamide on the physiological and phytotechnical characteristics of soybean plants subjected to the application of post-emergence herbicides. A randomized block experimental design was used, with eight treatments and four replicates. The treatments consisted of doses of 7.5 and 15 g ha−1 of thiamine, and doses of 22.5 and 45 g ha−1 of nicotinamide, associated with the herbicides Fomesafem (227.70 g a.i. ha-1) + S-Metolachlor (1.040,00 g a.i. ha-1) + Clomazone (540.00 g a.i. ha-1) and one treatment with only the herbicides. The physiological and phytotechnical characteristics were evaluated. For water use efficiency, the combination of thiamine and nicotinamide at doses of 7.5 g + 22.5 g ha-1 respectively, and 45 g ha-1 of nicotinamide resulted in a higher average, 10.70%, than the other treatments. For total chlorophyll and carotenoids, the application of thiamine at a dose of 7.5 g ha-1 was 26.80% and 53.0% higher than the other treatments, respectively. For production components, the treatments with a dose of 22.5 g ha-1 of nicotinamide (50N+H), the combination of thiamine and nicotinamide at a dose of 45 g ha-1 (100N100T+H) provided gains in relation to the herbicide treatment. The exogenous application of vitamins, thiamine and nicotinamide was able to mitigate the phytotoxic effect of the application of post-emergence herbicides in soybean crops, especially when nicotinamide was used at a dose of 22.5 g ha-1, which increased most pigments and production components.